Association of Genetic Polymorphisms in TNFRSF11 with the Progression of Genetic Susceptibility to Gastric Cancer. (22nd June 2020) - Fan, Yu; Gu, Xuyu; Pan, Huiwen; Dai, Zhe; Zou, Chen; Gao, Zhenjun; Zhang, Heng
Abstract : Objective . To investigate the relationship between polymorphism of TNFRSF11 gene rs9533156 and rs2277438 and susceptibility to gastric cancer. Methods . A case-control study was conducted to select 577 cases of primary gastric cancer and 678 cases of normal control. We extracted whole blood genomic DNA and amplified the target gene fragment by PCR. The genotyping and allele were tested through the snapshot method. Results . In this case-control study, we observed that there was a difference in the genotype distribution of TNFRSF11 gene rs9533156 between the case group and the control group. The frequency distribution of TC heterozygous mutation in the case group was higher than that in the control group. The smoking rate in the case group (34.49%) was higher than that in the control group (27.29%), and the difference in frequency distribution between the two groups was statistically significant (P = 0.006 ). Our findings suggest that TNFRSF11 rs9533156 is associated with susceptibility to GC, which is more evident among elderly patients (>62 years), nonsmokers, and patients who do not consume alcohol. The analysis of the relationship between the TNFSF11 gene rs9533156 site variant and clinical factors of gastric cancer showed that, compared with the tumor size <2 cm group, patients with tumor size ≥2 cm and whom carrying rs9533156 site mutations had a higher frequency distribution, and the difference was statistically significant (P = 0.022 ). Compared with the nonhyperglycemic group, the frequency distribution of patients with rs9533156 site mutations in the diabetes group was higher, and the difference was statistically significant (P < 0.001 ). Conclusion . This study shows that there is a correlation between smoking and the occurrence of gastric cancer. Based on our research, the functional SNP TNFRSF11 TC genotype may be an indicator of individual susceptibility to GC. The mutation at rs9533156 may be related to the size of gastric cancer. The mutation rate of rs9533156 of TNFSF11 gene is higher in diabetic gastric cancer patients.